2014
DOI: 10.1039/c4cp03068k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced catalytic and SERS activities of CTAB stabilized interconnected osmium nanoclusters

Abstract: A new route for the formation of osmium nanoparticles (NPs) having different morphologies like aggregated clusters, chain-like networks, and small spheres are reported. The synthesis was done by utilizing a simple wet-chemical method at room temperature (RT) by the reaction of OsO 4 , cetyl trimethyl ammonium bromide (CTAB), 2,7-dihydroxynaphthalene (2,7-DHN) and NaOH under 30 min of reaction. The diameter of the individual particles in all the morphologies was B1-3 nm. The synthesized materials have been test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 60 publications
5
55
0
Order By: Relevance
“…The nanoparticles aggregate to form long nanochains which show defective sites in the form of grooves or furrows which can act as active centers for catalysis . The morphological effect of osmium nanoclusters on the catalytic conversion of organic nitro aromatic compounds and the SERS studies was reported by S. Kundu and co‐workers . S. Sampath et al .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The nanoparticles aggregate to form long nanochains which show defective sites in the form of grooves or furrows which can act as active centers for catalysis . The morphological effect of osmium nanoclusters on the catalytic conversion of organic nitro aromatic compounds and the SERS studies was reported by S. Kundu and co‐workers . S. Sampath et al .…”
Section: Introductionmentioning
confidence: 91%
“…[10] The morphological effect of osmium nanoclusters on the catalytic conversion of organic nitro aromatic compounds and the SERS studies was reported by S. Kundu and co-workers. [11] S. Sampath et al demonstrated the importance of Iridium nanostructures on the SERS studies. [12] The literature on Rh nanoparticles synthesis and their catalytic behaviour are limited compared to Au and Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The peak observed at 3650 cm -1 represents the presence of pure CTAB and O-H stretching of the surfactant. The peak was also observed at 3337 cm-1 corresponding to N-H stretching vibration of CTAB capped onto the Pd nanoparticles[50]. Themethylene C-H stretching and anti-stretching vibration frequencies of pure CTAB are observed at 2880 and 2939cm −1 [50-51], while only a single peak shift was observed at 2875cm −1 in case of Pd nanoparticles, which indicates the presence of -CH 2 vibration of capping agent (surfactant) on the surface of Pd nanoparticle.…”
mentioning
confidence: 88%
“…With the advent of SERS, the limitation in Raman spectroscopic technique to recognize weak signals from noise signals were also solved. Some of the recent works [25][26][27][28] reported in the analysis of biomolecules using SERS highlights the importance of such studies with respect to advances in research. Molecular association of the iron oxide nanoparticles with protein and polysaccharide in presence of CTAB was probed using this technique.…”
Section: Introductionmentioning
confidence: 99%